2021
DOI: 10.1007/s11060-021-03788-6
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of laboratory prognostic scores for patients with radiosurgically treated brain metastases of non-pulmonary primary tumor

Abstract: Purpose To investigate the clinical value of the inflammation based prognostic scores for patients with radiosurgically treated brain metastases (BM) originating from non-pulmonary primary tumor (PT). Methods A retrospective analysis of 340 BM patients of different PT origin (melanoma, breast, gastrointestinal, or genitourinary cancer) was performed. Pre-radiosurgical laboratory prognostic scores, such as the Neutrophil-to-Lymphocyte Ratio (NLR), the Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…It enabled us to compute a threshold based on diseases’ progress and be different from the results obtained by benign disease patients as the control cohort. The obtained cut-offs for CEA, CA153, CA125, killer T cell, and LMR are slightly higher for those found in previous studies (CEA: 5 ng/ml, CA153: 31.3 U/ml, B cell%: literature range: 7%–23%, Th/Tc: literature range: 0.9-3.6, LMR: literature range: 3-5.5) ( 20 , 30 32 , 37 39 ). ROC analysis showed that the accuracy of a single marker for diagnosis of stage I-III BC patients and stage IV BC patients was not high (AUC <0.800).…”
Section: Discussioncontrasting
confidence: 51%
“…It enabled us to compute a threshold based on diseases’ progress and be different from the results obtained by benign disease patients as the control cohort. The obtained cut-offs for CEA, CA153, CA125, killer T cell, and LMR are slightly higher for those found in previous studies (CEA: 5 ng/ml, CA153: 31.3 U/ml, B cell%: literature range: 7%–23%, Th/Tc: literature range: 0.9-3.6, LMR: literature range: 3-5.5) ( 20 , 30 32 , 37 39 ). ROC analysis showed that the accuracy of a single marker for diagnosis of stage I-III BC patients and stage IV BC patients was not high (AUC <0.800).…”
Section: Discussioncontrasting
confidence: 51%
“…Comprehensive summary and retrospective evaluation of prognostic scores for patients with newly diagnosed brain metastases treated with upfront radiosurgery in a modern patient collective. Radiotherapy and Oncology, 172,[23][24][25][26][27][28][29][30][31]…”
mentioning
confidence: 99%
“…Regarding the NLR ≥5, patients with a low NLR may experience prolonged survival after WBRT for advanced non-SCLC [22]. Similarly, the NLR has been reported to be a prognostic factor after resection [12] and radiation therapy [13] in patients with BM. To the best of our knowledge, this is the rst study to examine the NLR in patients with cancer who underwent pWBRT.…”
Section: Discussionmentioning
confidence: 98%
“…LabBM score consists of hemoglobin, platelet count, LDH, and C-reactive protein (CRP) in addition to albumin. Because systemic in ammation was reported to be associated with cancer development and progression [13], NLR, serum albumin, and CRP may be important factors in the cancer journey. Hence, blood tests can provide an objective measure of the current status of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation